2018
DOI: 10.1634/theoncologist.2018-0263
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Protein Kinase Inhibitors Based on Tumor Tissue Kinase Activity Profiles in Patients with Refractory Solid Malignancies: An Interventional Molecular Profiling Study

Abstract: Lessons Learned. Clinically applicable tools are needed for treatment selection and repurposing of available protein kinase inhibitors (PKIs) in patients with advanced solid tumors refractory to standard treatment.Using a tyrosine kinase peptide substrate microarray, observed inhibitory activity in vitro could not sufficiently predict clinical benefit of treatment with the selected PKI.Background.This exploratory molecular profiling study determined the feasibility and benefit of the selection of protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated the role of tyrosine kinases in human diseases [55, 56]. Consequently, tyrosine kinases have become one of the main areas of pharmacological experiments intended to develop targeted drugs [57].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the role of tyrosine kinases in human diseases [55, 56]. Consequently, tyrosine kinases have become one of the main areas of pharmacological experiments intended to develop targeted drugs [57].…”
Section: Discussionmentioning
confidence: 99%
“…While these kinds of strategies are excellent for determining substrate specificity of kinases using e.g. immunoprecipitated or recombinant enzyme, they are less clear-cut when cell lysates are used, and so far have not shown clinical benefit in predicting tyrosine kinase inhibitor (TKI) treatment success (albeit in a small study that employed in vitro inhibitor treatment that may have been inconsistent with inhibitor levels in vivo) (Labots et al, 2018). On the other hand, studies measuring kinase activity in intact cells by monitoring an endogenous substrate via Western blot have shown a relationship between phosphorylation level and outcomes (White et al, 2007), supporting the idea that while they can be informative for some aspects of kinase biology, lysate-based kinase reactions may not model the drug/target interaction environment adequately enough to make clinical decisions.…”
Section: Measuring Tyrosine Kinase Activity When Substrates Aren't Knmentioning
confidence: 99%